Valproate lowers plasma concentration of olanzapine - Bergemann, Niels; Kress, Kai; Abu-Tair, Fatima; Frick, Alex; Kopitz, Jürgen (Journal of clinical psychopharmacology, 2006)
An abstract is unavailable.